RESPONCE OF PHYSICO-CHEMICAL SOIL PROPERTIES TO WASTEWATER APPLICATION AND SUBSEQUENT EFFECTS ON THREE WOODY SPECIES PLANTS - AMEDI, J. F.; RASHEED, R. O.; IBRAHIM, D.A. (Journal of Duhok University, 2021)
Water scarcity is a world-wide problem that is predict to increase as a result of increasing population and subsequent increasing the pressure on water sources. This research aimed to reach a feasible outcome for the possibility of blending industrial effluent with high quality water as a method of reducing the increasing demand on fresh water for irrigation. The study was conduct in the college of Agricultural engineering science- Forestry department from June till October of 2019 to examine the effect of blending wastewater of two types of industrial wastewater from different regions with tap water at three dilutions for each (25%, 50%, and 75%) along with the control. Factorial Randomized Complete Block Design (RCBD) was used to analyze the physical and chemical properties of water, soil and growth parameter of three species (Platanus orientalis L., Eucalyptus camaldulensis Dehn, and Populus nigra L.). The results revealed that the soil properties (temperature, pH, electrical conductivity, potassium, nitrate, bicarbonate, sulfate, chloride, and phosphate) were directly affected by water trends since pH of R2 ww. has an acidic nature (5.3) as well the soil irrigated with this wastewater record pH value lower than 6 in all months. The EC of R1 ww. record high values so as the soil irrigated with different dilutions of it which reach 2.5 ds.m-1 when the concentration was 75% which was significantly different from control soil (0.5 ds.m-1). Moreover, increasing the concentration of wastewater lead to form unfavorable soil for the growth of tested plants by recording lower root and shoot biomass when the concentration of wastewaters was > 25% as well as, the chlorophyl content which record an increment in eucalyptus in chlorophyl a, b, and total when irrigated with 25% R1 ww. and R2 ww. then a reduction observed when wastewater concentration increased. Aforementioned finding led to a conclusion that diluting wastewater with tap water increased the survival rate of plants and mitigate the properties of water which can be recommended to be used as a substitution for irrigation